The role play technique to develop speaking skills among students in second year of bachillerato “a” afternoon session at unidad educativa José Angel palacio in the city of Loja, during the 2018 – 2019 school year - Medina Guaman, Claudia Maritza (2019)
The general objective of this research work was to develop speaking skills through the Role Play Technique in the students of second year of Bachillerato “A” afternoon session at Unidad Educativa José Angel Palacio in the city of Loja during the 2018-2019 school year. The methods used were: scientific, descriptive, statistical and synthetic-analytical, which were used to gather, describe, represent, and analyze the data obtained. An observation sheet and field notes were used to register students’ behavior. Two tests and two questionnaires were applied to twelve students to record their knowledge. The results showed that students developed their speaking skills in the following aspects: grammar, vocabulary, fluency, pronunciation, and comprehension. In conclusion, the use of Role Play Technique helped students to reduce their fear of expressing orally their ideas in English.